2020
DOI: 10.1007/s11255-020-02615-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasound vs computed tomography scan for upper urinary tract malignancies and development of a risk-based diagnostic algorithm for haematuria in a UK tertiary centre

Abstract: Accuracy of ultrasound vs computed tomography scan for upper urinary tract malignancies and development of a risk-based diagnostic algorithm for haematuria in a UK tertiary centre', International urology and nephrology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Given the emerging evidence surrounding the low risk of upper-tract malignancies in patients with NVH and the risks to patients associated with CTU, there have been growing trends in the literature to limit the routine use of CTU for investigating patients with NVH, without careful consideration of the risks and benefits [16, 18, 19]. After previously recommending investigation with CTU for patients aged 35 and over, the AUA's guideline on the investigation of microhaematuria introduced in 2020 presents an algorithm for risk-stratifying NVH patients based on age, sex, haematuria presentation, and other risk factors for urothelial malignancy, with ultrasonography replacing CTU for upper-tract imaging in all but high-risk patients [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the emerging evidence surrounding the low risk of upper-tract malignancies in patients with NVH and the risks to patients associated with CTU, there have been growing trends in the literature to limit the routine use of CTU for investigating patients with NVH, without careful consideration of the risks and benefits [16, 18, 19]. After previously recommending investigation with CTU for patients aged 35 and over, the AUA's guideline on the investigation of microhaematuria introduced in 2020 presents an algorithm for risk-stratifying NVH patients based on age, sex, haematuria presentation, and other risk factors for urothelial malignancy, with ultrasonography replacing CTU for upper-tract imaging in all but high-risk patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…While smoking was a significant predictor in our univariate analysis, its non-significance in subsequent multivariate analysis may be explained by the lack of accurate quantification of smoking history available to us for analysis retrospectively. While similar investigation pathways have been proposed in the UK, none have yet to become incorporated into a guideline [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent retrospective study of 575 patients by David et al of a mixed but mainly gross hematuria group of high-risk patients whose ultrasounds were followed by CTU showed the diagnostic accuracy of ultrasound and CTU to be 95.8 and 99.1% respectively (8 renal cell carcinomas and 4 upper tract urothelial carcinomas) with both modalities demonstrating 100% sensitivity. 49 This study was strong in comparing both modalities but limited in the rather small number of actual carcinomas. Another recent study this one by Tan et al followed separate groups using either ultrasound or CTU but not both and found that CTU detected three times as many upper urinary tract malignancies (renal cell carcinoma and urothelial carcinoma) than ultrasound: 53/1692 (3.1%) vs 21/2166 (1.0%).…”
Section: First-line Ctu or Ultrasonography?mentioning
confidence: 93%